Phenotypic characterization of the native chicken variety maintained at Hosur - THIRUNAVUKKARASU, P; VASANTHAKUMAR, T; KANNAN, V (The Indian Journal of Animal Sciences, 2024)
The study on phenotypic characterization of the native chicken variety maintained at the College of Poultry Production and Management (CPPM), Hosur was studied as per directives by National Bureau of Animal Genetic Resources (NBAGR), Karnal, India. A sum of 540 male and 540 female day-old chicks (a total of 1080 chicks) were distributed randomly into three replicates of each sex having 180 chicks and reared up to 20 weeks of age. The morphological traits like feather morphology and distribution were normal. The plumage colour was predominantly brown followed by greyish black and brownish black with solid plumage pattern with yellow colour of skin and shank. The earlobe and comb colour was red. The male birds showed higher morphometric values in shank and keel length except for breast angle of the native chicken variety. Based on this study, it was concluded that the native chicken variety maintained at CPPM, Hosur is most suitable for backyard rearing by the farming community as its demand is showing increasing trend towards future.